Dampak Media Massa terhadap Terbentuknya Opini Masyarakat: Film Ice Cold: Murder, Coffee and Jessica Wongso di Netflix - Maria Septian Riasanti Mola (Jurnalistik dan Media, 2023)
This research explores the impact of mass media, specifically Netflix and its documentary series "Ice Cold: Murder, Coffee and Jessica Wongso", on public opinion concerning the cyanide coffee case and the justice system in Indonesia. Utilizing the Mass Society Theory as a theoretical foundation, the study employs methodologies involving document analysis, interviews, and online surveys to decipher how Netflix influences the viewers' perceptions of the case. Findings from the analysis suggest that Netflix influences public opinion through three major functions outlined in the Mass Society Theory: enforcement of social norms, the narcotising function, and confering status. Interviews with viewers provided insights into shifts in perceptions, with some spectators doubting the validity of the legal decision against Jessica and others viewing Netflix's portrayal as an attempt to revisit a case that was seemingly resolved. The study concludes that mass media platforms, such as Netflix, play a critical role in shaping public opinion. Documentary series like "Ice Cold: Murder, Coffee and Jessica Wongso" can potentially alter viewers' perspective, interrogate social norms and create a narcotising effect that could influence societal reactions to various issues, including the cyanide coffee case and the justice system in Indonesia. Future researchers may further explore similar impacts of Netflix's portrayals on public opinion in different contexts. Additionally, the public should cultivate their critical assessment skills when processing information presented by mass media, acknowledging potential interests, perspectives, and biases inherent in the news portrayal. Keywords: Mass Media, Public Opinion, Cyanide Coffee Case